Pengaruh Tata Kelola Perusahaan, Financial Distress Dan Free Cashflow Terhadap Manajemen Laba - Monica Azril; Nikhayani Nikhayani; Syawaliyah Nurus Salamah; Dien Noviany Rahmatika (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This study aims to analyze the influence of corporate governance, financial distress, and free cash flow on earnings management using a Systematic Literature Review (SLR) approach. A total of 76 articles published between 2020 and 2025 were examined based on topic relevance, research methods, and empirical findings. The results indicate that corporate governance—particularly through mechanisms such as independent commissioners, institutional ownership, audit committees, and audit quality—plays a significant role in reducing earnings manipulation by strengthening oversight functions. Financial distress is generally identified as a factor that encourages management to engage in earnings manipulation as an effort to maintain the appearance of financial stability, although several studies report inconsistent results depending on industry characteristics and company conditions. Free cash flow is also found to potentially trigger opportunistic managerial behavior, especially when internal monitoring is weak; however, its negative effect can be mitigated by effective corporate governance. Overall, this study concludes that earnings manipulation is influenced by the interaction of financial pressure, managerial discretion over cash flow, and the strength of corporate governance mechanisms. These findings contribute to strengthening governance practices and improving the quality of financial reporting in Indonesia.